Countering Islamophobia and Muslim Stereotypes in Ali Eteraz’s Native Believer - Shahbaz, Afia; Shaheen, Aamer; Qamar, Sadia (Pakistan Languages and Humanities Review, 2025)
This research paper attempts to delineate the strategies adopted by American Muslims to counter Islamophobia and Muslim Stereotypes in Ali Eteraz’s novel Native Believer (2016). Employing Sherene Razack’s theoretical perspectives from her book: Nothing has to Make Sense: Upholding White Supremacy through anti-Muslim Racism (2022), the paper focuses on post-9/11 Muslim lives in America and the worldwide. The paper charts M’s journey from being a secular Muslim toward a reckless tramp and then an American civilian completely assimilated into the American society. The colonial encounter between Western powers and Muslim-majority regions, spanning centuries of conquest, colonization and cultural imposition has left indelible marks on both the colonizer and the colonized. As the securitization of Islam, War on Terror, and proliferation of surveillance measures serve to perpetuate a cycle of suspicion and discrimination and affect Muslim communities living at diaporic spaces, the paper shows that generally a Muslim has to devise an assimilative approach to survive in such a society